2017
DOI: 10.1055/s-0043-112345
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Brain Angiotensin System Blockade as a Novel Drug Target in Pharmacological Treatment of Neuropsychiatric Disorders

Abstract: Retreat in psychiatric drug development results in innovative medication decline that might be at least partially overcome by adjunct therapy. New evidence from clinical studies has shown a possible role for brain Renin-Angiotensin System (RAS) in both affective and psychotic disorders. Simultaneously, rapidly accumulating data from basic studies indicate effectiveness of central RAS blockade in much broader range of neuropsychiatric disease. Recent findings implicate brain RAS, especially Angiotensin II (Ang … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 188 publications
(184 reference statements)
0
7
0
Order By: Relevance
“…In the presence of D4 receptor blockade with clozapine or olanzapine, it is likely that the natriuretic effects of ARBs will be increased, further supporting the concept of treating hypertension associated with antipsychotic dopamine receptor antagonists. Of note, a recent review suggest that inhibition of the brain angiotensin system can reduce psychosis, thus complementing the antipsychotic actions of D2‐like receptor antagonists . The mutant mouse with a non‐functional D2 receptor mutation also has increased BP due to increased vasoconstrictor effects of sympathetic nervous system activation and endothelin type B receptor activation …”
Section: Resultsmentioning
confidence: 99%
“…In the presence of D4 receptor blockade with clozapine or olanzapine, it is likely that the natriuretic effects of ARBs will be increased, further supporting the concept of treating hypertension associated with antipsychotic dopamine receptor antagonists. Of note, a recent review suggest that inhibition of the brain angiotensin system can reduce psychosis, thus complementing the antipsychotic actions of D2‐like receptor antagonists . The mutant mouse with a non‐functional D2 receptor mutation also has increased BP due to increased vasoconstrictor effects of sympathetic nervous system activation and endothelin type B receptor activation …”
Section: Resultsmentioning
confidence: 99%
“…The protective effects exerted by ACEIs and ARBs treatments in pre-clinical and clinical settings have supported the involvement of RAS in neuropsychiatric conditions as well ( 51 , 70 , 71 ). In animal models of Parkinson's disease induced by MPTP or 6-hydroxydopamine, administration of AT1 receptor antagonists like losartan and ACEIs such as perindopril prevented motor dysfunction and resulted in increased dopamine striatal levels and neuronal survival ( 72 76 ).…”
Section: Ace2-angiotensin (1-7)-mas Receptors Axis Role In Geriatric-mentioning
confidence: 88%
“…ACEIs and ARBs are commonly prescribed for hypertension, myocardial infarction, heart failure, and diabetic nephropathy ( 98 100 ). The discovery of the expression of RAS components in the brain stimulated the investigation of the potential effects of ACE inhibition and AT1 receptor antagonism on the physiopathology of neuropsychiatric disorders ( 71 ).…”
Section: Discussion: Challenges and Opportunitiesmentioning
confidence: 99%
“…In addition, evidence suggests that an abrupt suspension of ACE inhibitors in patients with COVID-19 and cardiovascular disease may result in clinical deterioration and worse outcomes ( 136 , 138 , 139 ). In addition, the results of some preclinical studies suggested that ACE inhibition shows promise in the mitigation of psychotic symptomatology and cognitive deficits ( 140 142 ). Furthermore, human studies have indicated that ACE inhibitors may have favorable effects on cognitive deficits in schizophrenia, possibly by modulating the cleavage of specific neuropeptides, such as substance P and neurotensin ( 141 , 142 ).…”
Section: Ace Polymorphismsmentioning
confidence: 99%
“…In addition, the results of some preclinical studies suggested that ACE inhibition shows promise in the mitigation of psychotic symptomatology and cognitive deficits ( 140 142 ). Furthermore, human studies have indicated that ACE inhibitors may have favorable effects on cognitive deficits in schizophrenia, possibly by modulating the cleavage of specific neuropeptides, such as substance P and neurotensin ( 141 , 142 ).…”
Section: Ace Polymorphismsmentioning
confidence: 99%